2003
DOI: 10.1177/0310057x0303100513
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic Management of the Parturient with Protein S Deficiency and Lumboperitoneal Shunt

Abstract: Protein S, a vitamin K-dependent plasma protein, is a cofactor for protein C, an essential component of the regulatory system of coagulation. We describe the anaesthetic management of a parturient with protein S deficiency and an indwelling lumboperitoneal shunt, which was placed following transverse and sagittal sinus thrombosis. She was treated with aspirin and enoxaparin during pregnancy and underwent caesarean section under general anaesthesia without complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Elevated plasma levels of d ‐dimer are associated with increased risk of future incident VTE 34 and plasma kallikrein has been associated with an increased risk for both arterial and venous thrombosis 35 . Of the anticoagulant proteins reported here, mild protein S deficiency has been associated with recurrent episodes of VTEs, 36,37 whilst inherited deficiencies of HCII have been reported that, in some cases, may be associated with an increased risk of VTE, though this is not always the case 38 …”
Section: Discussionmentioning
confidence: 83%
“…Elevated plasma levels of d ‐dimer are associated with increased risk of future incident VTE 34 and plasma kallikrein has been associated with an increased risk for both arterial and venous thrombosis 35 . Of the anticoagulant proteins reported here, mild protein S deficiency has been associated with recurrent episodes of VTEs, 36,37 whilst inherited deficiencies of HCII have been reported that, in some cases, may be associated with an increased risk of VTE, though this is not always the case 38 …”
Section: Discussionmentioning
confidence: 83%
“…PS deficiency is an uncommon condition characterized by reduced PS activity, a serine protease present in blood plasma that holds intricate roles in coagulation, inflammation, and apoptosis (VTE) [1]. There are three distinct forms of PS deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…PS deficiency commonly manifests as VTE and recurrent pregnancy loss, with arterial thrombosis being a rare occurrence [1]. Here, we present a case involving inherited PS deficiency resulting in extensive arterial thrombosis of the bilateral lower limb.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Al margen de la técnica anestésica que se elija, se debe dar prioridad a la monitorización y evitar la disminución del gasto cardiaco, hipotermia, hipovolemia intraoperatoria y hemorragias, ya que esto se asocia a mayor riesgo de trombosis en pacientes con déficit de proteína S. La profilaxis posparto debe mantenerse por lo menos durante seis semanas con HBPM. [5][6][7] Se decidió realizar la técnica espinal en esta paciente debido a su sencillez, a la calidad anestésica y al pequeño calibre de la aguja utilizada. Sin embargo, al alta se debió considerar continuar con tromboprofilaxis, dado el riesgo de desarrollar alg un evento tromboembólico durante el estado puerperal.…”
Section: Discussionunclassified